(untitled) (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2022)
In this article we present the discrete SIR fractional model, as an alternative to the study of epidemiologic problems and developing mathematical modeling. In particular, we applied the fractional model to determine the basic reproduction number 𝑅0 of COVID-19 by adjusting curves over a period of the 250 days. The time considered is relative to the first wave of COVID-19 in 2020 in the state of Maranhão, Brazil. With the values of 𝑅0 it is possible to know better this disease so that more efficient measures are taken against it.